Combined optical and acoustic resolution photoacoustic microscopy - Moothanchery, Mohesh (2017)
Photoacoustic imaging is a fast growing in vivo imaging modality combining the optical absorption contrast and high spatial ultrasonic resolution. Using this technique deeper tissue penetration greater than optical mean free path (~1 mm in skin) is possible. Low resolution with deep penetration depth is possible utilizing acoustic focusing and high resolution with shallow imaging depth can be possible by optical focusing using different photoacoustic microscopy (PAM) systems. Here, we present a combined/switchable optical resolution and acoustic resolution photoacoustic microscopy (OR-AR-PAM) system capable of both high resolution and low resolution deep tissue imaging on the same sample. Lateral resolution of 3.9 μm using optical focusing and lateral resolution of 57 μm using acoustic focusing was successfully demonstrated using the combined system.